The Filipino can ; Accident or murder ; Flying high [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
The Philippines finishes the SEA Games in second overall with 91 gold medal haul. A bus runs over a 13 year old boy in Ozamis. But people there say, Lilian Bus Lines has a policy of "atrasan" to make sure victims die to save on survivors that cost more. A story about excellence and the advances made by aircraft technology. Features the Lufthansa, the German Airline.
The Filipino can (12 min.) -- Accident or murder (17 min.) -- Flying high (14 min.)
VHS.
Keywords: Lufthansa Airlines (Germany).; Lilian Bus Lines (Ozamis Oriental).; Southeast Asian Games (16th : 1991 : Philippines).; Athletes -- Philippines; Transportation -- Accidents; Airframes; Aircraft industry -- Technological innovations